Micro responses to macro shocks - Martín Almuzara; Victor Sancibrián (Federal Reserve Bank of New York, 2024)
We study estimation and inference in panel data regression models when the regressors of interest are macro shocks, which speaks to a large empirical literature that targets impulse responses via local projections. Our results hold under general dynamics and are uniformly valid over the degree of signal-tonoise of aggregate shocks. We show that the regression scores feature strong cross-sectional dependence and a known autocorrelation structure induced only by leads of the regressor. In general, including lags as controls and then clustering over the cross-section leads to simple, robust inference.
Keywords: C32; C33; C38; C51; 330; panel data; local projections; impulse responses; aggregate shocks; inference; heterogeneity